Apoyo social, funcionalidad familiar y riesgo de ulceración en pies de pacientes diabéticos tipo 2 atendidos en el Hospital Belén de Trujillo 2017 - Mercedes Chávez, Fredix Eriberto (2019)
The study entitled “Social support, family functionality and risk of ulceration in the feet of type 2 diabetic patients treated at the Hospital Belén de Trujillo 2017” has the general objective of determining whether there is a relationship between social support, family functionality and the risk of foot ulceration of type 2 diabetic patients, from the Diabetes program of the Hospital Belén de Trujillo 2017. This is a prospective, cross-sectional and comparative study that will be performed on 130 diabetic patients. The FACES III Family Functionality questionnaire will be applied to determine the type of functionality. The MOS social support questionnaire will be applied to establish the level of social support and a clinical examination of the feet will be performed and the Michigan test will be done to each one to determine the risk of ulceration. The non-parametric criteria independence test will be used, using the chi-square distribution with a significance level of 5% to see the relationship between the variables.